Artillery shells, 1940-1945
1940 1939-1945 "Artillery shells, 1940-1945" [HFR0176], c. 1940-1945 The Portuguese caption to this poster reads in English 'Millions and millions of artillery shells are being produced in British factories in one continuous torrent to help stop the Nazi aggression'. The Ministry of Information produced propaganda posters and leaflets in several languages for circulation in Europe and the Colonies.